Ferroelectric and pyroelectric properties of form IV Poly (Vinylidene Fluoride) and its composites / Gan Wee Chen - Gan, Wee Chen (2015)

(untitled)
The studies on ferroelectric and pyroelectric properties of the poly(vinylidene fluoride), PVDF and its composites in this work are mainly divided into three parts. In the first part, ferroelectric and pyroelectric properties of PVDF, were investigated with special interest on its Form IV thin films prepared by spin-coating cast from acetone and methyl ethyl ketone onto glass substrate. These solvents have low boiling points and low permittivities yielded mostly Form II thin films. Annealing at 140 o C induced a marked increase in crystallinity and reduce the surface roughness of the thin films. The Form II PVDF thin film was completely transformed to Form IV after the application of high electric field greater than 200 MV/m. The D-E hysteresis loops that were associated with the ferroelectric polarization reversal in Form IV crystalline regions were observed by using alternating electric field, E. The remanent polarization Pr reached a maximum of 70 mC/m2 with a coercive field Ec of 200 MV/m. The pyroelectric coefficient py determined after hysteresis loop measurement was shown to be proportional to Pr, and reached py of 28 μC/m2K. In the second part, thin films of a ferroelectric polymer matrix made of PVDF incorporated with a non-ferroelectric inclusion, TiO2, were prepared with different weight fractions (0-30 wt%). The dielectric and pyroelectric properties of the PVDF/TiO2 composite thin films are measured as a function of several annealing temperatures (60 o C to 140 o C). Theoretical models, including Maxwell, Clausius-Mossotti, Furukawa and EMT were employed to describe the effective dielectric permittivity of the composites. This part of the work also studies the effect of a non-ferroelectric inclusion, which contributed to the enhancement of pyroelectric activity after the poling process, in a ferroelectric polymer matrix based composite. An increase in the dc conductivity of the polymer matrix led to an iv easier poling process and reduced the required poling electric field from 260 MV/m to 120 MV/m. The pyroelectric coefficient of the polymer composite has been enhanced by 26 % at a much lower poling electric field. In the third part, PVDF/La2O3 composite thin films were prepared by spin-coating method. It is found that the pyroelectric coefficient and remanent polarization of the composites were significantly improved to 42 μC/m2K and 84 mC/m2, respectively. The enhancement of the measured coefficients in the composites can be achieved by introducing a very small amount (3 wt%) of La2O3. Local field in the inclusion site has shown to facilitate the poling procedure. A simple Maxwell-Wagner model, which takes into consideration of the effect of the dc conductivity of the inclusion in the thin film composite, shows a good agreement with the obtained pyroelectric and ferroelectric properties.